Exploring hierarchy simplification for non-significant region removal - Borlido, Isabela; Fonseca, Gabriel B.; Patrocinio Jr, Zenilton; Cousty, Jean; Perret, Benjamin; Najman, Laurent; Kenmochi, Yukiko; Guimaraes, Silvio (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2019: Anais da XXXII Conference on Graphics, Patterns and Images, 2019)
Image segmentation is a classic subject in the field of digital image processing, and it can be used to solve a large variety of problems or serve as preprocessing for other methods of image analysis. The use of hierarchical image segmentation methods, which provide a multiscale representation that can be seen as a series of image segmentations, is a very common approach. The main idea of these methods is to produce a nested set of image segmentations in which a result at a given level can be produced by merging regions of the segmentation at its previous level. However, a hierarchy representation may produce small components at its higher levels, leading to oversegmentations on such scales. To solve this problem, we explore strategies to simplify hierarchies in order to remove non-significant regions, in terms of area, while trying to preserve the hierarchical structure. We evaluate the proposed simplification strategies with different hierarchical segmentation methods on the Pascal Context dataset by using precision-recall measures and fragmentation curve, along with a qualitative assessment showing that the simplification of hierarchies can lead to visually better image segmentations.